2001
DOI: 10.1161/hc2301.092122
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Endothelial Progenitor Cells in Patients With Acute Myocardial Infarction

Abstract: Background-Endothelial progenitor cells (EPCs) circulate in adult peripheral blood (PB) and contribute to neovascularization. However, little is known regarding whether EPCs and their putative precursor, CD34-positive mononuclear cells (MNC CD34ϩ ), are mobilized into PB in acute ischemic events in humans. Methods and Results-Flow cytometry revealed that circulating MNC CD34ϩ counts significantly increased in patients with acute myocardial infarction (nϭ16), peaking on day 7 after onset, whereas they were unch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
658
4
34

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,062 publications
(738 citation statements)
references
References 13 publications
37
658
4
34
Order By: Relevance
“…Similar results reported that vasculogenesis-related progenitor cells were increased in coronary heart diseases. 12 Taken together with ours, these results suggest that retinal ischaemic signal may stimulate bone marrow by certain systemic factors that are diffused into systemic circulation, and CD34 þ MNCs were subsequently mobilized into peripheral blood and differentiated into endothelial cells on ischaemic foci. Even though these consequences of EPC elevation in diabetic patients are only speculative, our results have significance in the demonstration of EPC elevation in diabetic patients in vivo.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar results reported that vasculogenesis-related progenitor cells were increased in coronary heart diseases. 12 Taken together with ours, these results suggest that retinal ischaemic signal may stimulate bone marrow by certain systemic factors that are diffused into systemic circulation, and CD34 þ MNCs were subsequently mobilized into peripheral blood and differentiated into endothelial cells on ischaemic foci. Even though these consequences of EPC elevation in diabetic patients are only speculative, our results have significance in the demonstration of EPC elevation in diabetic patients in vivo.…”
Section: Discussionsupporting
confidence: 82%
“…Previous reports demonstrated the therapeutic potential of EPC transplantation in animal models of hindlimb and myocardial ischaemia. 12 However, EPC elevation seems to be less helpful or harmful to diabetic retinopathy. Tepper et al 32 reported that diabetic EPCs exhibit alterations in functions important for blood vessel growth and may represent a mechanism by which diabetic EPCs are impaired in their ability to form collaterals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two distinct types of stem cells are currently known to reside within adult bone marrow: hematopoietic and mesenchymal stem cells. Shintani et al (2001) showed that the mobilization of CD34 + hematopoietic cells may be an important physiologic mechanism of cardiac tissue repair after heart failure. Other studies indicated that bone marrowderived mesenchymal stem cells when introduced into adult mouse or rat hearts integrated into myocardium and exhibited a myocyte phenotype (Tomita et al, 1999;Toma et al, 2002).…”
Section: Introductionmentioning
confidence: 99%